PEMBERDAYAAN KELOMPOK DASAWISMA DALAM PEMANFAATAN TANAMAN OBAT KELUARGA (TOGA) DI KELURAHAN KENALI ASAM BAWAH - Nurfitriani Nurfitriani; Tina Yuli Fatmawati (Jurnal Abdimas Kesehatan (JAK), 2019)
One program that can be implemented by the community in an effort to improve family welfare, especially in the field of  food is the planting and utilization program of Family Medicinal Plants (TOGA). TOGA is a home-grown plant that has medicinal properties. TOGA planting can be done in pots or on land around the house. The Kelurahan Kenali Asam Bawah  is one of the Kelurahan in Kota Baru Subdistrict where the community in the region generally still has a large enough yard, so that the utilization and management of the environment can be optimized by planting TOGA. Based on field observations, the Dasawiwma group did not have a pilot family of medicinal plants. Some of them also do not understand the efficacy of TOGA scientifically. Therefore it is necessary to conduct socialization / counseling about the efficacy of TOGA so that people can have knowledge about the efficacy of TOGA. The target of this community service activity is the dasawisma group d RT 047 The target target is 10 people in one dasawima group especially in Kelurahan Kenali Asam Bawah. The aim of community service is expected after participating in the socialization of Dasawisma The group leader is able to understand and be willing to motivate his group members about the importance of planting TOGA. The results obtained with the procurement of plants and the socialization of the use of the TOGA 100% increased knowledge of the participants